Unpacking the physical literacy concept for K-12 physical education: What should we expect the learner to master? - E. Paul Roetert; Lynn Couturier MacDonald (Elsevier, 2015)
The term "physical literacy" is gaining traction in many countries and institutions as a goal for physical education. This paper explores the concept of physical literacy and highlights the foundational work in this area, particularly that of Margaret Whitehead. The relationship of physical literacy to physical education is also discussed with potential ramifications for teachers and learners who adopt physical literacy as the goal of the subject area.